Association between insulin resistance and the magnetic resonance spectroscopy-determined marrow fat fraction in nondiabetic postmenopausal women. Issue 6 (June 2018) - Li, Guanwu; Xu, Zheng; Lin, Haiyang; Chen, Yilei; Li, Xuefeng; Chang, Shixin
Abstract: Objective: The clinical consequences of insulin resistance and hyperinsulinemia on marrow lipid remain elusive. We aimed to explore the effects of anthropometric and biochemical measures, that is, estimates of insulin resistance, on marrow lipid accumulation in nondiabetic postmenopausal women using magnetic resonance (MR) spectroscopy. Methods: The study participants were 91 nondiabetic postmenopausal women. Marrow fat fraction (FF) at the L3 vertebral body by single-voxel MR spectroscopy and bone mineral density (BMD) by dual-energy x-ray absorptiometry were measured. Their glucose and lipid metabolism were determined by biochemical analysis, and their insulin sensitivity was evaluated using the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR). Results: Adjusted for multiple covariates including age, years since menopause, body mass index, alcohol intake, tobacco use, physical activity, and serum lipid profile, the mean FF was significantly increased, and BMD at the lumbar spine, femoral neck, and total hip decreased as quartiles of HOMA-IR increased ( P for trends <0.01). HOMA-IR had a positive association with FF (mean difference 0.300, P < 0.001) and a negative association with BMD at the lumbar spine (mean difference −0.182, P = 0.016), total hip (mean difference −0.219, P = 0.001), and femoral neck (mean difference −0.195, P = 0.013). The above described associations of HOMA-IR with FF, lumbar spine, and total hip BMD remained essentially unchanged; however, the association with femoral neck BMD lost significance after adjusting for the aforementioned confounders. Conclusion: In nondiabetic postmenopausal women, insulin resistance is correlated with marrow lipid expansion. This association persists after adjusting for the body mass index and other potential covariates, suggesting an independent effect of insulin resistance on marrow adiposity.